Principles of Rational Food (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The draft Health Code of the Republic of Uzbekistan was developed by the Ministry of Health.The draft code also includes a section on key terms and concepts in the field of health. The health care system and the organization of medical care are covered in detail.The Code stipulates the regulation of medical and pharmaceutical activities, the determination of the type and volume of services provided. The rights and obligations of the parties to legal relations in the field of health care, as well as the legal regulation of certain types of medical and pharmaceutical activities, are defined.